Orbit/CLASP Is Required for Myosin Accumulation at the Cleavage Furrow in Drosophila Male Meiosis. - Kitazawa, D.; Matsuo, T.; Kaizuka, K.; Miyauchi, C.; Hayashi, D.; Inoue, Y.H. (PLoS ONE, 2014)
Peripheral microtubules (MTs) near the cell cortex are essential for the positioning and continuous constriction of the contractile ring (CR) in cytokinesis. Time-lapse observations of Drosophila male meiosis showed that myosin II was first recruited along the cell cortex independent of MTs. Then, shortly after peripheral MTs made contact with the equatorial cortex, myosin II was concentrated there in a narrow band. After MT contact, anillin and F-actin abruptly appeared on the equatorial cortex, simultaneously with myosin accumulation. We found that the accumulation of myosin did not require centralspindlin, but was instead dependent on Orbit, a Drosophila ortholog of the MT plus-end tracking protein CLASP. This protein is required for stabilization of central spindle MTs, which are essential for cytokinesis. Orbit was also localized in a mid-zone of peripheral MTs, and was concentrated in a ring at the equatorial cortex during late anaphase. Fluorescence resonance energy transfer experiments indicated that Orbit is closely associated with F-actin in the CR. We also showed that the myosin heavy chain was in close proximity with Orbit in the cleavage furrow region. Centralspindlin was dispensable in Orbit ring formation. Instead, the Polo-KLP3A/Feo complex was required for the Orbit accumulation independently of the Orbit MT-binding domain. However, orbit mutations of consensus sites for the phosphorylation of Cdk1 or Polo did not influence the Orbit accumulation, suggesting an indirect regulatory role of these protein kinases in Orbit localization. Orbit was also necessary for the maintenance of the CR. Our data suggest that Orbit plays an essential role as a connector between MTs and the CR in Drosophila male meiosis.